Acceptance of mobile money by poor citizens of India: integrating trust into the technology acceptance model. Issue 3 (11th May 2015) - Chauhan, Sumedha
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to understand the acceptance of mobile-money (m-money) among target populations, i.e. below-poverty-line citizens in India, using the technology acceptance model (TAM). The m-money service is a major initiative that can enable the provision of low-cost and speedy money transfer through mobile phones, especially in developing countries such as India. For a large section of the population in India, m-money can act as a way to achieve financial inclusion. However, for m-money to succeed, users should accept the initiative wholeheartedly. Design/methodology/approach – The survey data were collected from 225 actual and prospective m-money users and analysed using partial least square technique. Findings – The findings imply that the trust and the core constructs of TAM such as perceived usefulness, trust and attitude towards usage contribute in influencing the intention to accept m-money. Perceived ease of use neither impacts perceived usefulness nor attitude towards usage. Practical implications – This research also provides possible explanations for the significant relationships between the constructs and discusses how this information can be used to enhance the acceptance of m-money among poor Indians. Originality/value – This research is original and is based on primary data collection and its interpretation. It provides thorough empirical insights on the acceptance of m-money among poor Indian citizens which is currently a weakly addressed and empirically less explored area of research.